Hantu dan Bisnis Media; (Analisa Fenomena Tayangan Mistik di Media dengan Pendekatan Metode Komunikasi Terapan) - Hakiki, Kiki Muhamad (AL-ADYAN, 2019)
The focus of this paper is to examine the phenomenon of the rise of mystical shows in the media - both electronic and print media with a communication science theory approach namely the "Uses and Gratifications Theory" theory initiated by Katherine Miller in her book "Theories of Media Processing and Effects". With this theory we will find out why a media broadcasts certain programs excessively, even though they are sometimes not very good in terms of improving the education of the audience or readers. From the results of the study found facts bring; First, this phenomenon arises due to the conditions of modern human crisis which prioritize the materiality and forget the spirituality; Second, wrong understanding of Islamic mysticism (Sufism); Third, there are still many Indonesian people who are on the line of poverty and ignorance that must be eliminated from the battle of the modern world